Pemimpin Ormas Keagamaan Sebagai Man of Communion dalam Situasi Konflik Menurut Paus Benediktus XV dan Paus Yohanes XXIII - Tjatur Raharso, Aphonsus (Religió: Jurnal Studi Agama-agama, 2017)
Abstract This article is written out of a concern about the religious leadership trend performed by some Islamic mass organization leaders during the first three month of 2017 in Jakarta which ended in horizontal conflicts and frictions based on religious and racial issues. Through the comparative method, this article would show the leadership role model of Catholic religious leaders, especially two Catholic popes during the World War I and II era, Pope Benedict XV and Pope John XXIII. While the world leaders were confronting to each other and created blocks to provoke wars, the both popes were present as fathers who loved and embraced all humankind across the nations. They placed themselves as the peace makers and invited the world to build peaceful co-habitation, which respected human right, as well as imposed justice for all humankind. The both popes were man of communion and sign of peace in amid of world conflicts. To be man of communion and sign of peace, the religious leaders need to restrain themselves to not be affected by the conflict issues that make them be sectarian, extremist, partisan, or partial. When there is a conflict because of any factors, the religious mass organization leaders might only observe whether there is a violation of human right, justice or bonum commune. If there is any, regardless from which race, religion, and class the victims are, they should fight for the justice, invoke human right, and generate bonum commune based on the legal law, by encouraging peace and harmony in the society. [Artikel ini lahir dari sebuah keprihatinan mengenai model kepemimpinan religius yang ditampilkan oleh beberapa pemimpin ormas keagamaan Islam pada trimester pertama tahun 2017 di ibukota Jakarta dan berakhir pada gesekan dan konflik horisontal berdasarkan suku dan agama. Artikel ini ditulis dengan menggunakan metode komparatif, yakni dilakukan dengan menggali gaya kepemimpinan religius pemuka agama Katolik, khususnya dua orang Paus Gereja Katolik di masa Perang Dunia pertama dan kedua, yakni Benediktus XV dan Yohanes XXIII. Kedua Paus itu tampil sebagai bapa yang mencintai dan merangkul semua orang dan bangsa, menjadi juru-damai, serta mengajak para pemimpin bangsa untuk membangun cohabitation yang damai, yang menghormati hak dan martabat pribadi manusia, serta menegakkan keadilan bagi semua orang. Kedua Paus itu telah menjadi man of communion dan sign of peace yang efektif dalam situasi konflik mondial. Dari studi komparatif dapat ditemukan bahwa untuk bisa menjadi man of communion dan sign of peace dalam situasi konflik para pemimpin ormas keagamaan di Indonesia perlu menahan diri agar tidak terkooptasi dan menjadi sektarian, partisan atau parsialistik di hadapan dan di dalam kelompok yang dipimpinnya sendiri. Dalam konflik karena faktor apapun, para pemimpin ormas keagamaan hanya boleh mengawasi apakah terjadi pelanggaran terhadap hak asasi manusia, keadilan, atau bonum commune.]